Timing of Antiretroviral Therapy for HIV-1 Infection and Tuberculosis - Havlir, Diane V; Kendall, Michelle A; Ive, Prudence; Kumwenda, Johnstone; Swindells, Susan; Qasba, Sarojini S; Luetkemeyer, Anne F; Hogg, Evelyn; Rooney, James F; Wu, Xingye; Hosseinipour, Mina C; Lalloo, Umesh; et al. (The New England journal of medicine, 2011)
In this international study involving 809 patients with HIV and TB coinfection, earlier therapy for both infections, versus waiting 8 to 12 weeks to initiate antiretrovirals after anti-TB therapy, was beneficial in patients with a low CD4+ T-cell count (<50 per cubic millimeter). The treatment of patients with tuberculosis and newly identified infection with human immunodeficiency virus type 1 (HIV-1) is one of the most challenging aspects of HIV medicine. Antiretroviral therapy (ART) must be started during treatment for tuberculosis, 1 , 2 yet starting ART very early in the course of tuberculosis therapy increases the pill burden, the potential drug toxicity, and the risk of tuberculosis-associated immune reconstitution inflammatory syndrome (IRIS). 3 , 4 For these reasons, programs, providers, and patients are reluctant to initiate ART during the intensive 8-week induction phase of tuberculosis therapy, when the pill burden and toxicity of tuberculosis medications are greatest. . . .